A well-tempered heart : a novel - Sendker, Jan-Philipp (Other Press, 2014)
Almost ten years have passed since Julia Win came back from Burma, her father's native country. Though she is a successful Manhattan lawyer, her private life is at a crossroads. Her boyfriend has recently left her and she is, despite her wealth, unhappy with her professional life. Julia is lost and exhausted. One day, in the middle of an important business meeting, she hears a stranger's voice in her head that causes her to leave the office without explanation. In the following days, her crisis only deepens. Not only does the female voice refuse to disappear, but it starts to ask questions Julia has been trying to avoid. Why do you live alone? To whom do you feel close? What do you want in life? Interwoven with Julia's story is that of a Burmese woman named Nu Nu who finds her world turned upside down when Burma goes to war and calls on her two young sons to be child soldiers. This spirited sequel, like Sendker's first novel, The Art of Hearing Heartbeats, explores the most inspiring and passionate terrain: the human heart.